Ziprasidone-induced stuttering： a case report - Sun Zhenxiao; Liu Huaxue (Sichuan jingshen weisheng, 2022)
This paper reported a case of a 25-year-old male schizophrenic patient， who obtained remission from psychotic symptoms during the treatment of olanzapine and trihexylphenidyl， was given ziprasidone treatment additionally due to the occurrence of auditory hallucination， and developed stuttering 4 days later. The stuttering disappeared 2 days following the discontinuation of therapy， and reappeared after reinstitution of ziprasidone therapy， but disappeared again after discontinuation. The dose of olanzapine was increased to 20 mg/d to ensure the stability of psychotic remission. At a follow-up visit 4 months later， the patient’s mental condition was stable and stuttering did not recur， indicating that the stuttering was induced by ziprasidone. This case suggests that the possibility of stuttering as an adverse reaction should be considered in the clinical application of ziprasidone.